Climate change, food security and sustainable human development in Nigeria: A critical reflection - Chinyeake J. Igbokwe-Ibeto (Africa’s Public Service Delivery & Performance Review, 2019)
Background: Nigeria is abundant in numerous agro-ecological resources, which should make it a major exporter of food items in the world. Regrettably, it has become a major food importer as a result of food scarcity. The state of food production in the country is worsened by the phenomena of climate change and global warming. These developments have deleterious effects on agricultural activities in general and food production in particular. While there are policies and agencies in the country to combat these developments, it appears they have proved ineffective in the face of increasing inconsistency in government policies, climate change and global warming. The effect of all these phenomena on human development cannot be overemphasised. A nation that cannot feed its population cannot promote development.